2014
DOI: 10.3758/s13421-014-0426-x
|View full text |Cite
|
Sign up to set email alerts
|

Generality of a congruity effect in judgements of relative order

Abstract: The judgement of relative order (JOR) procedure is used to investigate serial-order memory. Measuring response times, the wording of the instructions (whether the earlier or the later item was designated as the target) reversed the direction of search in subspan lists (Chan, Ross, Earle, & Caplan Psychonomic Bulletin & Review, 16(5), 945-951, 2009). If a similar congruity effect applied to above-span lists and, furthermore, with error rate as the measure, this could suggest how to model order memory across sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 64 publications
3
25
2
Order By: Relevance
“…Unsurprisingly, their JOR task replicated the canonical results from relative JOR, with correct RTs failing to show an e↵ect of the lag to the less recent probe, consistent with a backward self-terminating scanning model. Remarkably, however, when the instructions were reversed the pattern of results for correct RTs was consistent with a forward selfterminating scanning model (see also Liu, Chan, & Caplan, 2014). This suggests that a temporally-organized representation can be accessed strategically.…”
Section: Is Scanning Under Strategic Control?supporting
confidence: 77%
See 1 more Smart Citation
“…Unsurprisingly, their JOR task replicated the canonical results from relative JOR, with correct RTs failing to show an e↵ect of the lag to the less recent probe, consistent with a backward self-terminating scanning model. Remarkably, however, when the instructions were reversed the pattern of results for correct RTs was consistent with a forward selfterminating scanning model (see also Liu, Chan, & Caplan, 2014). This suggests that a temporally-organized representation can be accessed strategically.…”
Section: Is Scanning Under Strategic Control?supporting
confidence: 77%
“…Similarly, the minimal dependence of judged recency on previous presentations of a stimulus (Hintzman, 2010) is a natural consequence of a backward self-terminating model. The forward scanning results (Chan et al, 2009;Liu et al, 2014) could result from recovery of the temporal context at the start of the list (Davelaar, Goshen-Gottstein, Ashkenazi, Haarmann, & Usher, 2005) followed by a forward scan using a translation operator (Shankar, Singh, & Howard, 2016). The major gap in reconciling short-term (this study, Muter, 1979;Hacker, 1980;Hockley, 1984;McElree & Dosher, 1993) and long-term (Hinrichs & Buschke, 1968;Hintzman, 2010;Yntema & Trask, 1963) JORs is the lack of RT data for judgments over scales more than a few seconds.…”
Section: A Common Model For Jors Across Scales?mentioning
confidence: 94%
“…To maintain continuity with previous studies (Chan, Ross, Earle, & Caplan, 2009;Liu, Chan, & Caplan, 2014), stimuli were 16 consonants (excluding S, W, X, and Z) from the English alphabet displayed in uppercase. Each list comprised nine consonants drawn at random without replacement from the stimulus pool.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…The experiment was implemented with the Python Experiment-Programming Library (PyEPL; Geller et al, 2007). The procedure for the Control condition was identical to Liu et al's (2014) judgements of relative order experiment, but with list length 9 and a serial-recall test. Depending on grouping, participants were either asked to type the list in forward or backward order: (a) Excerpt from "forward" instruction: ".…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…In the case of judgments of relative order, that stimulus dimension (time or position) may thus function very much like any other stimulus dimension, as Brown et al (2007) proposed. Liu et al (2014) found that the congruity effect could be well fit by a self-terminating search model (Hacker, 1980;McElree, 2006) if it could switch directions depending on the instruction (searching the list in the forward direction for the earlier instruction and in the backward direction for the later instruction), but only at short list lengths. They noted that the Hacker (1980) sequential, selfterminating search model saved response time when list-items were unavailable in memory, but they could find no published model that would actually save any time in this way.…”
Section: The Congruity Effect In Judgments Of Relative Order and Consmentioning
confidence: 99%